Teaching urban sensing skills – experiences from a summer school - Åse Håtveit; Simone Mora; Titus Venverloo; Fábio Duarte; Monica Divitini (Interaction Design and Architecture(s))
Sustainability has become an important topic in higher edu- cation, with low-cost and open-source sensing platforms for urban monitoring emerging as tools to engage students in formal and informal learning experiences. In this context, we present our experience with the design and implementation of a five-day summer school aimed at teaching urban sensing techniques. The summer school engaged graduate students from diverse disciplines, including engineering, architecture, environmental science, and social science. Participants gained hands-on experience with designing and executing urban sensing experiments to investigate research questions developed by the participants, using an open-source urban sensing platform provided to the students. They also developed scientific literacy skills such as problem elaboration, data visualization, and communication with non-experts. The impact of the summer school was evaluated via interviews, digital surveys, and author observations, unveiling three key themes: effective teaching practices for urban mapping tools, factors inhibiting learning, and factors promoting scientific literacy. We discuss how our findings can be applied to the development of similar learning initiatives.